Development of a double-stranded siRNA labelling method by using 99mTc and single photon emission computed tomography imaging. (7th February 2017) - Kano, Daisuke; Nakagami, Yoshihiro; Kurihara, Hiroaki; Hosokawa, Shota; Zenda, Sadamoto; Kusumoto, Masahiko; Fujii, Hirofumi; Kaneta, Tomohiro; Saito, Shinichiro; Uesawa, Yoshihiro; Kagaya, Hajime
Abstract: In vivo biodistribution of small interfering RNAs (siRNAs) is important to develop them for medical use. Therefore, novel single photon emitter-labelled siRNA was prepared by using diethylenetriamine- N, N, N ′, N ″, N ″-pentaacetic acid (DTPA) and poly(A) polymerase, and subsequently, real-time analysis of siRNA trafficking was performed by using single photon emission computed tomography (SPECT). This study aimed at assessing the use of 99m Tc-radiolabelled siRNA targeting lacZ to detect lacZ expression in vivo . siRNA targeting lacZ was radiolabelled with 99m Tc by using the bifunctional chelator DTPA, and the labelling efficiency and specific activity were determined. The probe stability in RNaseA was assessed. SPECT imaging was performed in mice overexpressing the lacZ gene in the liver. Radiolabelled siRNA remained highly stable in RNaseA solution at 37 °C. In SPECT imaging, significant 99m Tc accumulation in the liver was observed in mice overexpressing the lacZ gene. 99m Tc-labelled lacZ siRNA shows β-galactosidase-specific accumulation and appears promising for the visualisation of lacZ expression in vivo . Our labelled siRNA should be deliverable to specific regions overexpressing the target gene.